Pregnancy course in patients with intrahepatic cholestasis of pregnancy treated with very low doses of ursodeoxycholic acid. (2nd January 2016) - Grymowicz, Monika; Czajkowski, Krzysztof; Smolarczyk, Roman
Abstract: Objective. Ursodeoxycholic acid (UDCA) has been proposed as the optimal pharmacological treatment for intrahepatic cholestasis of pregnancy (ICP). The lowest effective dosage of UDCA in women with ICP has not been established. The objective is to determine the risk of adverse pregnancy outcomes resulting from ICP and to measure changes in liver function parameters and pruritus severity in ICP patients treated with low doses of UDCA. Material and methods. ICP was diagnosed in 203 patients on the basis of pruritus and elevated liver biochemical parameters. Patients with total bile acids (TBA) ≥10 μmol/l ( n = 157) received UDCA (300–450 mg/day; 4–6 mg/kg/day) until delivery. Maternal and fetal outcomes of women with ICP were compared with 100 patients without cholestasis. Patients with ICP were hospitalized for treatment and fetal surveillance. Results. There was no correlation between fetal and neonatal complication rates in ICP patients and biochemical markers of cholestasis. Significant declines in serum TBA ( p = 0.003), bilirubin concentration ( p = 0.026) and aminotransferase activity ( p < 0.001) were observed during treatment with low doses of UDCA. Moreover, severity of pruritus was ameliorated during the 2 weeks of therapy ( p = 0.037). A total of 17 patients (10.9%) did not respond to treatment. Conclusions. UDCA at low doses improved biochemical markers and clinical symptoms in almost 90% of ICP patients.